Agriculture and rural development policy in the country’s industrial and modernization - Bùi Thị Bích Thuận (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In the process of industrialization and modernization of the country, the Party and State have always paid attention to the development of agriculture and rural areas and have adopted many correct guidelines and policies suitable to reality. Thanks to that, our country’s agriculture and rural areas have achieved many important achievements in recent years, but there are still some limitations and difficulties. In the context of rapid industrialization; Industrial Revolution 4.0 and digital transformation have a strong impact; Natural disasters and epidemics are increasingly complicated, the 13th Party Congress and the Prime Minister’s "Strategy for sustainable agricultural and rural development for the period of 2021 - 2030, with a vision to 2050" of the Prime Minister closely, on that basis, the article mentions some solutions to develop agriculture and rural areas in the current period.